Study of the Effect of Cryoprotectants on Liposomes of Canine Spermatozoa Total Lipids - Linnik, T. P.; Dyubko, T. S.; Yegorov, M. I.; Pivovarenko, V. G. (Problems of Cryobiology and Cryomedicine, 2007)
The mechanism of interaction between the cryoprotective agents (CPAs): ethylene glycol (EG), glycerol and N,N-dimethylformamide (DMFA) with lipid bilayer of liposomes formed from total lipids of canine spermatozoa by fluorescent spectroscopy using new fluorescent probe of flavonoid origin: 3-hydroxy-4â€™-(N,N-dimethylamine)flavon (FME). It has been established that among the studied CPAs (glycerol, EG, DMFA) the highest effect on the form of FME fluorescence spectrum associated to lipid bilayer is rendered by DMFA. The effect rate of the studies CPAs on liposomes is determined by hydrophobic-hydrophilic balance of their molecules. DMFA predominantly affects lipid bilayer by hydrophobic interaction, and glycerol and EG mainly influence hydrate layer of polar â€œheadsâ€ of phospholipids by forming intermolecular hydrogen bonds.